2018
DOI: 10.3389/fmicb.2018.01594
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity and Mechanism of Action of the Co(III) Coordination Complexes With Diamine Chelate Ligands Against Reference and Clinical Strains of Candida spp.

Abstract: Although many antifungal agents are available in clinical treatment, increasing resistance of fungi, especially Candida species, to the available drugs requires the development of new safe and non-toxic compounds with novel modes of action as effective treatment against resistant microorganisms. Cobalt complexes are very interesting and attractive as potential candidates with antimicrobial activity. Their therapeutic uses as antiviral, antibacterial antifungal, antiparasitic, antitumour, transferrin transporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 63 publications
2
69
0
3
Order By: Relevance
“…In a study involving several Candida species, C. glabrata had the most sensitive MIC and MHC ranges for cobalt treatment. The study concluded that this was due to its inability to form hyphae [14].…”
Section: Albicansmentioning
confidence: 99%
“…In a study involving several Candida species, C. glabrata had the most sensitive MIC and MHC ranges for cobalt treatment. The study concluded that this was due to its inability to form hyphae [14].…”
Section: Albicansmentioning
confidence: 99%
“…Furthermore, amino acids act as biocompatible ligands to enhance the therapeutic and medicinal applications of metal complexes. Cobalt(III) amino acid complexes find various applications, such as antifungal (Turecka et al, 2018), antimicrobial (Lv et al, 2006), antibacterial (Stnil et al, 2011) and anticancer agents (Munteanu & Suntharalingam, 2015). Despite many potential applications, conglomerate crystallization catalysed by cobalt(III) was reported more than a decade ago and has since suffered a hiatus.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive candidiasis are considered the life-threatening infections associated with high morbidity and mortality (Pappas et al 2016;Hacioglu et al 2018). The mortality rate of bloodstream infections caused by these yeasts was reported to be as high as 40-60% among immunosuppressed and hospitalized patients (Sun et al 2015;Li et al 2018;Turecka et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of fungal infection is increasing, especially in populations of immunosuppressed individuals (persons with HIV/AIDS or primary immune deficiency) and due to the continuous development of modern medicines, such as organ transplantation, hemodialysis, parenteral nutrition, extensive applicability of catheters or medical implants, cancer chemotherapy, and the widespread use of broad-spectrum antibiotics, glucocorticoids, and immunosuppressants (Turecka et al 2018;Roemer and Krysan 2014;Gomes da Silva Dantas et al 2018). In addition to the predisposing factors of the host, the pathogenicity of Candida species is affected by their virulence factors, such as the polymorphism (growth in two forms, unicellular and filamentous), production of extracellular enzymes (proteases, phospholipases, and hemolysins), as well as the expression of adhesins, which is related to the biofilm formation (on host tissues or on medical device surfaces) (Hacioglu et al 2018;Sun et al 2015;Li et al 2018;Gomes da Silva Dantas et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation